Study of jet shapes in inclusive jet production in pp collisions at √s=7TeV using the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acharya, B; et al. (2011)
Jet shapes have been measured in inclusive jet production in proton-proton collisions at √s=7TeV using 3pb-1 of data recorded by the ATLAS experiment at the LHC. Jets are reconstructed using the anti-kt algorithm with transverse momentum 30GeV